Branching pattern of terminal branches of the facial nerve: A cadaveric study - A K Sapna (Wolters Kluwer Medknow Publications, 2021)
Background: For a successful facial surgery, it is vital to have a good knowledge of the distribution of the facial nerve in the face. The aim of this study was to highlight the pattern in the branching of the end part of the facial nerve in adults and fetuses and to look for any anastomoses between them. The branching pattern in the two groups is compared for any significant association. Methodology: Cross sectional study done in cadavers and stillborn fetuses. Subjects and Methods: Done in 100 facial halves. Statistical Analysis Used: Chi square test is used to look for any significant association between the branching pattern and gender & side of the face. Results: The branching pattern was classified into six types as per Davis et al. classification in the two study groups - adults and fetuses. The frequencies of occurrence in the first group were Type I - 1%, Type II - 7%, Type III - 18%, Type IV - 17%, Type V - 4%, and Type VI - 3% and in the second group were Type I - 1%, Type II - 8%, Type III - 20%, Type IV - 15%, Type V - 5%, and Type VI - 1%. No significant association was found in the branching pattern with respect to gender and side of the face in the two groups of study. Conclusions: There are multiple anastomotic communications among the end branches of the facial nerve. More the anatomical knowledge of these communications, lesser will be any unwanted facial nerve injury.